Isolation and Characterization of a Novel Myophage Abp9 Against Pandrug Resistant Acinetobacater baumannii - Jiang, Lingli; Tan, Jingjie; Hao, Yi; Wang, Qi; Yan, Xiaorui; Wang, Dali; Tuo, Li; Wei, Zairong; Huang, Guangtao (Frontiers in Microbiology, 2020)
Acinetobacter baumannii (A. baumannii) has emerged as one of the most troublesome pathogens in health care institutions. A. baumannii can cause a wide range of diseases in humans, including pneumonia and septicemia. Phage therapy has drawn great interest from medical researchers as a potential way to control infections by antibiotic-resistant A. baumannii. Using a pandrug-resistant clinical A. baumannii isolate ABZY9 as an indicator, we isolated a lytic phage Abp9 from hospital sewage. Abp9 belongs to myoviridae family and shows a wider host range of 12%. Abp9 contains a linear double-stranded DNA genome of 44,820 bp with a G+C content of 37.69%. The Abp9 genome contains 80 open reading frames,but lacks any known virulence genes or lysogen-formation genes.In a systemic A. baumannii infection mouse models, Abp9 treatment showed good therapeutic effects. We have also observed an excellent lytic activity against A. baumannii in biofilm form of growth in vitro. All of these suggest that Abp9 is a good candidate for the phage therapy against drug-resistant A. baumannii infections.